Long-term genetic consequences of mammal reintroductions into an Australian conservation reserve. (March 2018) - White, Lauren C.; Moseby, Katherine E.; Thomson, Vicki A.; Donnellan, Stephen C.; Austin, Jeremy J.
Abstract: Reintroduction programs aim to restore self-sustaining populations of threatened species to their historic range. However, demographic restoration may not reflect genetic restoration, which is necessary for the long-term persistence of populations. Four threatened Australian mammals, the greater stick-nest rat ( Leporillus conditor ), greater bilby ( Macrotis lagotis ), burrowing bettong ( Bettongia lesueur ) and western barred bandicoot ( Perameles bougainville ), were reintroduced at Arid Recovery Reserve in northern South Australia over the last 18 years. These reintroductions have been deemed successful based on population growth and persistence, however the genetic consequences of the reintroductions are not known. We generated large single nucleotide polymorphism (SNP) datasets for each species currently at Arid Recovery and compared them to samples collected from founders. We found that average genetic diversity in all populations at the Arid Recovery Reserve are close to, or exceeding, the levels measured in the founders. Increased genetic diversity in two species was achieved by admixing slightly diverged and inbred source populations. Our results suggest that genetic diversity in translocated populations can be improved or maintained over relatively long time frames, even in small conservation reserves, and highlight the power of admixture as a tool for conservation management.